Seasonal diets of camels, cattle, sheep, and goats in a common range in eastern Africa - Migongo-Bake, W.; Hansen, R.M. (1987)
A study on the seasonal diets of camels, cattle, sheep, and goats in a common range in northern Kenya carried to gather information as a basis for better management of the Semi-Arid rangelands of eastern Africa.